(untitled) (Strathmore Law Journal, 2016)
In 2008 the first Chief Prosecutor of the International Criminal Court (‘the Court’ or ‘ICC’) Luis Moreno Ocampo, had shifted his prosecutorial strategy with regard to the situation in Sudan by deciding to pursue the serving President of Sudan, Omar al Bashir, whereas before, his strategy had been to request the Pre-Trial Chamber to issue summons for persons deemed to be mid-level individuals in the Khartoum government. Acting on that referral, the Prosecutor initiated investigations into the situation in Darfur beginning June 2005. On 14 July 2008, the Prosecutor filed an application requesting the Pre-Trial Chamber to issue a warrant of arrest against President Bashir, which was granted on 4 March 2009. Subsequently, warrants of arrest were issued for Al Bashir on 4 March 2009 and on 12 July 2010, with the second warrant being issued to reflect the inclusion of the charge of genocide in the indictment. This article examines how this "Great Escape", on the light of the last events.